Thermal and mechanical properties of gamma-irradiated prevulcanized natural rubber latex/low nitrosamines latex blends. Issue 11 (1st December 2016) - Ibrahim, Pairu; Daik, Rusli; Wan Zin, Wan Manshol
ABSTRACT: Thermal and mechanical properties of blended radiation prevulcanized natural rubber latex (RVNRL) and low nitrosamines latex (LNL) were studied. RVNRL was blended with LNL at various composition ratios. From the tensile test, it was found that the optimum tensile value was attained at a total blending ratio of 70% RVNRL and 30% LNL. Latex blending with optimum tensile strength was then subjected to gamma irradiation at various doses with the presence and absence of methyl methacrylate (MMA) at 10 pphr. It was found that the gamma irradiation of latex blend with the presence of MMA could help increase further the tensile value. Composition of blending at a specific ratio and gamma irradiation at a specific dose has led to a significant improvement in the mechanical properties of the latex blend. The formation of grafting in the latex blend was characterized by Fourier transform infrared spectra (FTIR) spectroscopy and differential scanning calorimetry (DSC). FTIR spectroscopy confirmed that MMA could be grafted onto blended latex effectively under appropriate irradiation conditions. Two new peaks at 1731 and 1149 cm −1 were observed after irradiation, indicating the presence of an ester group from poly(methyl methacrylate) (PMMA), which was grafted onto rubber chains. This finding was proved by the presence of new T g in DSC analysis. The increase in new T g indicates the movement of grafting chains, which are tightly bound onto rubber chains.